ANALISIS IMPLEMENTASI PELAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) DI PUSKESMAS KOTA SALATIGA - Rida Krita Imaroh; Ayun Sriatmi; Antono Suryoputro (Jurnal Kesehatan Masyarakat (Undip), 2018)
Voluntary Counseling and Testing (VCT) is one of the early way to detect HIV for people. The services include pre-test counseling, HIV testing, and post-test counseling. The implementation of VCT service in Salatiga is’t optimal yet, it’s provide by the decrease of VCT service visit in the whole public helath center in Salatiga. This research intends to analyze the implementation of VCT service by community health clinic. It’s a qualitative research which got by doing deep interview to six main informants and fourteen triangulation informants. The research variable includes analysis of the implementation of VCT service by the health staff, based on aspects of communication, resources, disposition, characteristic of the executive body and the aspects of economy, social, and politic environment support. The outcome of the research shows that the service implementation of VCT by public health center’s staff is still unsatisfactory. The Matter is caused by the VCT teams of the whole public health center have no case management, so tasks haven’t been shared by the case management. Counselor in public health center hasn’t implemented the procedures completely and even hasn’t SOP yet. The atitude of the health staff is felts less friendly and make the patients reluctant to return again, even sometimes they’re expelled from the public health center. The VCT team hasn’t been consistent in service scheduling. Examination room is narrow and mixed with another infectious disease that make the patients feel uncomfortable. Related to stigma of the society that still considers percussion with the VCT service.